Electric pulse toughening method of ray shielding ceramic material
The WAlB ceramic is processed through the control parameters of the electrical pulse technology, which improves its toughness and bending resistance, solves the brittleness of ceramic materials, and provides an efficient and green toughening method suitable for ray shielding ceramic materials.
Patent Information
- Application Number
- CN202411289952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-14
AI Technical Summary
WAlB ceramic materials have severe brittleness due to intrinsic defects, which limits their wide application in the field of nuclear technology. The existing toughening methods have limitations, such as limited particle diffusion toughening effect, complex whisker or fiber toughening process and high cost. Phase change toughening has limited effect in high temperature environments.
The WAlB ceramic material is processed through electrical pulse technology to regulate the coupling effect of current, pulse period, pulse width and frequency, and improve the toughness and bending resistance of the ceramic. The specific steps include fixing the WAlB ceramic material on the copper electrode, setting electrical pulse parameters such as the average current is 15A, the pulse width is 100μs, and the pulse period is 2500μs, and performing electrical pulse processing.
It significantly improves the flexural strength and flexural strain of WAlB ceramics, solves the problem of material brittleness, and provides an efficient and green toughening method without affecting its high temperature stability.
Smart Images

Figure CN119191880A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to an electric pulse toughening method for a ray shielding ceramic material. Background Art
[0002] WAlB ceramics, a functional and structural integrated radiation shielding material, have important applications in nuclear technology fields such as reactors and accelerators. However, due to the presence of many intrinsic defects in WAlB ceramics, the resulting brittleness of the material severely limits its widespread application. In the prior art, the toughening of ceramic materials is mainly based on the perspective of ceramic design. By regulating the microstructure of the ceramic, the purpose of preventing the formation and expansion of cracks in the ceramic is achieved, thereby improving performance. However, the synthesis condition window of WAlB ceramics is narrow, and slight changes in the synthesis conditions seriously affect the formation of the WAlB phase structure.
[0003] According to the current research status at home and abroad, the toughening methods of ceramic materials mainly include particle dispersion toughening, whisker or fiber toughening, phase change toughening, self-toughening, composite toughening, etc., but the above toughening methods still have many limitations. For example, the preparation process of particle dispersion toughening is simple, but the toughening effect is limited, and the high-temperature performance of ductile metal particle toughened ceramic materials is poor; although whisker or fiber toughening has a good toughening effect, the preparation process is complex and the cost is high, and it is difficult to evenly distribute whiskers or fibers in the matrix; phase change toughening has a strong temperature sensitivity, and the toughening effect is limited in high temperature environments, or even fails.
[0004] Therefore, it is necessary to develop a toughening method for ray shielding WAlB ceramic materials that has good toughening effect and does not affect its high temperature stability. Summary of the invention
[0005] In order to solve the brittleness problem of WAlB ceramics as a structural and functional integrated radiation shielding material, the purpose of the present invention is to provide an electric pulse toughening method for radiation shielding ceramic materials. By utilizing the good conductivity of WAlB ceramics and through ceramic post-processing, electric pulse technology is introduced to toughen the intrinsic brittle WAlB ceramics, and the toughening effect of WAlB ceramic materials is achieved by controlling the coupling effect between electric pulse technology parameters such as current, pulse period, pulse width, and frequency.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides an electric pulse toughening method for a ray shielding ceramic material, comprising the following steps:
[0008] (1) Fixing the two ends of the WAlB ceramic material polished on both sides to the copper electrode through the copper plate, and the copper electrode is connected to the pulse current generator;
[0009] (2) setting the electrical pulse parameters, including: average current of 15 A, pulse width of 100 μs, pulse period of 2500 μs, and pulse loading time of 10-60 s;
[0010] (3) Performing electric pulse treatment on the WAlB ceramic material according to the electric pulse parameters and removing it after completion.
[0011] Preferably, in step (1), the WAlB ceramic material is rectangular, with dimensions of length×width×thickness of 10 mm×2 mm×0.7 mm.
[0012] Preferably, in step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, and pulse loading time of 20-40s.
[0013] Preferably, in step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, each pulse time of 10s, sample cooling time as the interval between two pulses, and pulse loading time of 10-60s in total.
[0014] More preferably, in step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, each pulse time of 10s, sample cooling time as the interval between two pulses, and pulse loading time of 20-40s in total.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The present invention proposes an electric pulse toughening method for ray shielding ceramic materials. The mutual coupling between electric pulse technical parameters such as current, pulse period, pulse width, and frequency is crucial to ceramic toughening. During the electric pulse toughening process, the loading time of the pulse current has a particularly significant effect on the toughening. By adjusting the pulse time to determine the optimal electric pulse toughening technical parameter combination for toughening WAlB ceramics, the toughness and bending resistance of WAlB ceramics are improved to varying degrees, effectively solving the brittleness problem of WAlB as a structural and functional integrated ray shielding material, and at the same time providing an efficient and green method for toughening the same type of ceramic materials.
[0017] 2. The electric pulse toughening technology is introduced for the conductive WAlB ceramic material. The bending strength and bending strain are significantly improved compared with those before the electric pulse treatment. After 20s of pulse current treatment with a peak current of 340A, a pulse width of 100μs, and a pulse period of 2500μs, the bending performance of WAlB ceramics is significantly improved, and its bending strength and bending strain are increased by 88% and 725% respectively compared with those before the electric pulse treatment.
[0018] 3. The toughening effect of WAlB ceramic materials is evaluated by controlling the coupling effect between the parameters of the electric pulse toughening technology, such as current, pulse period, pulse width, and frequency. The three-point bending test is used to test the bending resistance of ceramics loaded with electric pulse technology. Then, the pulse time and pulse action mode are regulated. The toughening effect is good without affecting its high-temperature stability. The method is simple and flexible. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The geometrical settings of the electric pulse treatment in the embodiment and the monitored surface temperature and peak current changes of the WAlB sample.
[0020] Figure 2 1 is the stress-strain curve of the WAlB sample before and after the electric pulse treatment when the current is 15A in the embodiment.
[0021] Figure 3 Surface morphology SEM images of different electric pulse durations when the current is 15 A (a) no pulse, (b) 10 s, (c) 20 s, and (d) 30 s; (eh) are enlarged images of the area indicated by the square in (ad); and cross-sectional SEM images of different electric pulse durations (i) no pulse, (j) 10 s, (k) 20 s, and (l) 30 s.
[0022] Figure 4 Phase evolution in WAlB after electric pulse when the current is 15A in the embodiment; (a) HADDF image of the original sample, corresponding EDS scan (b) W and (c) Al; (d) HADDF image of electric pulse 20s, corresponding EDS scan (e) W and (f) Al, (g) is the HRTEM image of the square area marked in (d), and (h) is the FTF of (g); (i) HADDF image of electric pulse 30s, corresponding EDS scan (j) W and (k) Al, (l) is the HRTEM image of the square area marked in (i), and (m) is the FTF of (l). Circles and squares represent WB and Al, respectively. DETAILED DESCRIPTION
[0023] In order to more fully understand and demonstrate the technical solutions, purposes and advantages of the present invention, the technical effects produced by the present invention are further described in detail and completely in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all. It should be pointed out that for those of ordinary skill in the art, other embodiments obtained without departing from the concept of the present invention all belong to the protection scope of the present invention, and the present invention is specifically described in conjunction with the accompanying drawings and embodiments.
[0024] Unless otherwise specified in the following examples, all reagents and materials used were commercially available.
[0025] Example 1
[0026] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0027] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0028] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, and pulse loading time is 10s.
[0029] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0030] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0031] According to the test, the bending strain of WAlB ceramic material after electric pulse treatment reached 0.35%, and the bending strength was 366MPa, which were increased by 250% and 88% respectively compared with the samples without electric pulse loading.
[0032] Example 2
[0033] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0034] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0035] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, each pulse time is 10s, sample cooling time is used as the interval between two pulses, and pulse loading time is 20s in total.
[0036] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0037] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0038] According to the test, after the electric pulse treatment, the bending strain of the WAlB ceramic material reached 0.83%, and the bending strength was 354MPa, which were increased by 730% and 82% respectively compared with the samples without electric pulse loading.
[0039] Example 3
[0040] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0041] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0042] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, each pulse time is 10s, sample cooling time is used as the interval between two pulses, and pulse loading time is 30s in total.
[0043] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0044] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0045] According to the test, after the electric pulse treatment, the bending strain of the WAlB ceramic material reached 0.43%, and the bending strength was 355MPa, which were increased by 330% and 82% respectively compared with those without electric pulse loading.
[0046] like Figure 1-4 As shown, Figure 1 Geometric setup for electrical pulse processing and monitored sample surface temperature and peak current; Figure 2 The stress-strain curves of WAlB samples before and after electric pulse treatment at a current of 15A; Figure 3Surface morphology SEM images of different electric pulse durations when the current is 15A (a) no pulse, (b) 10s, (c) 20s, (d) 30s; (eh) are enlarged images of the area indicated by the square in (ad); cross-sectional SEM images of different electric pulse durations (i) no pulse, (j) 10s, (k) 20s, (l) 30s; Figure 4 Phase evolution in WAlB after electric pulse at current of 15A; (a) HADDF image of original sample, corresponding EDS scan of (b) W and (c) Al; (d) HADDF image of electric pulse for 20s, corresponding EDS scan of (e) W and (f) Al, (g) HRTEM image of the square area marked in (d), (h) FTF of (g); (i) HADDF image of electric pulse for 30s, corresponding EDS scan of (j) W and (k) Al, (l) HRTEM image of the square area marked in (i), (m) FTF of (l), circles and squares represent WB and Al, respectively.
[0047] Example 4
[0048] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0049] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0050] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, each pulse time is 10s, sample cooling time is used as the interval between two pulses, and pulse loading time is 40s in total.
[0051] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0052] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0053] According to the test, after the electric pulse treatment, the bending strain of the WAlB ceramic material reached 0.5%, and the bending strength was 374MPa, which were increased by 400% and 92% respectively compared with those without electric pulse loading.
[0054] Example 5
[0055] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0056] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0057] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, each pulse time is 10s, sample cooling time is used as the interval between two pulses, and pulse loading time is 60s in total.
[0058] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0059] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0060] According to the test, after the electric pulse treatment, the bending strain of the WAlB ceramic material reached 0.32%, and the bending strength was 332MPa, which were increased by 220% and 70% respectively compared with those without electric pulse loading.
[0061] Example 6
[0062] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0063] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0064] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, and electric pulse continuous loading time is 20s.
[0065] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0066] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0067] According to the test, after the electric pulse treatment, the bending strain of the WAlB ceramic material reached 0.29% and the bending strength was 269MPa, which were increased by 190% and 38% respectively compared with those without electric pulse loading.
[0068] Example 7
[0069] This embodiment provides a method for electric pulse toughening of a radiation shielding ceramic material, the steps of which are as follows:
[0070] Step 1. Fix the two ends of a WAlB ceramic rectangular sample with a size of 10mm×2mm×0.7mm (length×width×thickness) polished on both sides on copper electrodes through two copper plates, and the copper electrodes are connected to a pulse current generator. Measure the surface resistance of the sample before fixing, take the average value of multiple measurements, and continuously monitor the surface temperature of the sample with a k-type thermocouple DP-700.
[0071] Step 2: Set the electric pulse parameters, specifically: average current is 15A, pulse width is 100μs, pulse period is 2500μs, and electric pulse continuous loading time is 60s.
[0072] Step 3: Perform electric pulse treatment, remove the sample after completion, measure the surface resistance of the sample again, and take the average value after multiple measurements.
[0073] Step 4: Use a universal testing machine to measure the bending resistance of the samples after electric pulse treatment. Repeat the test three times for the samples with the same electric pulse loading conditions to ensure the reliability of the test.
[0074] According to the test, the bending strain of WAlB ceramic material after electric pulse treatment reached 0.35%, and the bending strength was 290MPa, which were increased by 250% and 49% respectively compared with those without electric pulse loading.
[0075] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for electric pulse toughening of radiation shielding ceramic materials, characterized in that: The following steps are involved: (1) Fixing the two ends of the WAlB ceramic material polished on both sides to the copper electrode through the copper plate, and the copper electrode is connected to the pulse current generator; (2) setting the electrical pulse parameters, including: average current of 15 A, pulse width of 100 μs, pulse period of 2500 μs, and pulse loading time of 10-60 s; (3) Performing electric pulse treatment on the WAlB ceramic material according to the electric pulse parameters and removing it after completion.
2. The electric pulse toughening method for radiation shielding ceramic materials according to claim 1, characterized in that: In step (1), the WAlB ceramic material is rectangular, and the dimensions of length×width×thickness are 10 mm×2 mm×0.7 mm.
3. The electric pulse toughening method for radiation shielding ceramic materials according to claim 1, characterized in that: In step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, and pulse loading time of 20-40s.
4. The electric pulse toughening method for radiation shielding ceramic materials according to claim 1, characterized in that: In step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, each pulse time of 10s, sample cooling time as the interval between two pulses, and pulse loading time of 10-60s in total.
5. The electric pulse toughening method for radiation shielding ceramic materials according to claim 4, characterized in that: In step (2), the electric pulse parameters include: average current of 15A, pulse width of 100μs, pulse period of 2500μs, each pulse time of 10s, sample cooling time as the interval between two pulses, and pulse loading time of 20-40s in total.
Citation Information
Patent Citations
Carbon nano tube reinforced AlMgB14-TiB2 composite material and preparation method thereof
CN102531609A
High remanent polarization BNT-based ferroelectric ceramic material and preparation method and application thereof
CN115677343A
Device and method for infiltrating and sintering gradient blade tip wear-resistant coating through electric pulse driving
CN116497353A
Improved materials for tungsten boride neutron shields
CN116670784A
Method for producing porous bioceramic wollastonite
RU2743834C1
